Exploring Ethnomathematics in Local Culture: A Bridge Between Tradition and Classroom Mathematics - Sandi , Eric Krisna (Aksioma Education Journal, 2025)
This study explores the mathematical knowledge embedded in local cultural practices and examines how such knowledge can be meaningfully integrated into formal mathematics education through the lens of ethnomathematics. Using a qualitative descriptive approach grounded in educational ethnography, the research was conducted in a culturally rich Indonesian community known for its traditional crafts, architecture, and rituals. Data were collected through participant observation, in-depth interviews with artisans, teachers, and students, as well as analysis of cultural artifacts and curriculum documents. The findings reveal that traditional practices such as weaving, house building, and ritual organization contain rich mathematical concepts, including geometry, symmetry, measurement, ratios, and logical structuring. These forms of knowledge, although informal, align closely with school-level mathematics. Students showed greater engagement and understanding when learning mathematics through culturally relevant contexts. However, the integration of ethnomathematics faces challenges such as lack of resources, teacher training, and curricular support. The study recommends the development of culturally responsive teaching frameworks and stronger collaboration between schools and local communities to promote inclusive and meaningful mathematics learning.